ESTRUTURA DA COMUNIDADE DE MACROINVERTEBRADOS BENTÔNICOS EM UM CÓRREGO DA BACIA DO RIO IGUATEMI, MATO GROSSO DO SUL - SOUZA, M. C. O; BATISTA-SILVA, V. F. B.; CRUZ, F. I.; MOREIRA, R.; BONETO, D. D. (ANAIS DO ENIC, 2016)
-